DETECTION AND MOLECULAR CHARACTERIZATION OF ORCHIDS INFECTING VIRUSES IN INDONESIA - daryono, B. S. (2011)
Survey of viral diseases of orchid plants conducted in Java and Bali during June-August 2010 showed that various genera of orchids grown in the areas was symptomatically affected by a few kind of mosaic disease. The plants showed chlorotic, mosaic or ring-spot symptoms on leaves. Simplex RT-PCR assay confirmed that three orchids from diffrent location was positively infected by a virus related to Cymbidium mosaic virus (CymMV) infection. A multiplex RT-PCR method was developed for detection of CymMV and ORSV in orchids. Specific primers were designed based on the avaible sequences of CymMV and ORSV from the GenBank and were used to RT-PCR amplify the respective viral coat protein genes.